RETRACTED: Effect of Weekly Long-Acting Growth Hormone Replacement Therapy Compared to Daily Growth Hormone on Children With Short Stature: A Meta-Analysis - Ma, Liyan; Li, Liangyi; Pan, Wen; Huang, Congfu; Liu, Limei; Zhang, Xiaoxiao (Frontiers in Endocrinology, 2021)
Background We performed a meta-analysis to evaluate the efficacy and safety of weekly long-acting growth hormone replacement therapy compared to daily growth hormone in children with short stature. Methods A systematic literature search up to April 2021 was done and 11 studies included 1232 children with short stature treated with growth hormone replacement therapy at the start of the study; 737 of them were using weekly long-acting growth hormone replacement therapy and 495 were using daily growth hormone. They were reporting relationships between the efficacy and safety of long-acting growth hormone replacement therapy and daily growth hormone in children with short stature. We calculated the odds ratio (OR), and mean difference (MD) with 95% confidence intervals (CIs) to assess the efficacy and safety of weekly long-acting growth hormone replacement therapy compared to daily growth hormone in children with short stature using the dichotomous or continuous method with a random or fixed-effect model. Results Long-acting growth hormone replacement therapy had significantly lower height standard deviation scores chronological age (MD, -0.10; 95% CI, -0.13- -0.08, p<0.001), and insulin-like growth factor binding protein-3 (MD, -0.69; 95% CI, -1.09- -0.30, p<0.001) compared to daily growth hormone in children with short stature. However, growth hormone replacement therapy had no significantly difference in height velocity (MD, -0.09; 95% CI, -0.69-0.5, p=0.76), height standard deviation scores bone age (MD, -0.04; 95% CI, -0.10-0.02, p=0.16), insulin-like growth factor 1 standard deviation scores (MD, 0.26; 95% CI, -0.26-0.79, p=0.33), and incidence of adverse events (OR, 1.16; 95% CI, 0.90-1.50, p=0.25) compared to daily growth hormone in children with short stature. Conclusions Long-acting growth hormone replacement therapy had significantly lower height standard deviation scores chronological age, and insulin-like growth factor binding protein-3 compared to daily growth hormone in children with short stature. However, growth hormone replacement therapy had no significant difference in height velocity, height standard deviation scores bone age, insulin-like growth factor 1 standard deviation scores, and incidence of adverse events compared to daily growth hormone in children with short stature. Furthers studies are required to validate these findings.